2012
DOI: 10.1016/j.ntt.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Repeated antenatal corticosteroid treatments adversely affect neural transmission time and auditory thresholds in laboratory rats

Abstract: Antenatal corticosteroid (AC) treatment is given to pregnant women at risk for preterm birth to reduce infant morbidity and mortality by enhancing lung and brain maturation. However, there is no accepted regimen on how frequently AC treatments should be given and some studies found that repeated AC treatments can cause growth retardation and brain damage. Our goal was to assess the dose-dependent effects of repeated AC treatment and estimate the critical number of AC courses to cause harmful effects on the aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 97 publications
7
17
0
Order By: Relevance
“…Dunlop and Quinlivan examined the effect of repeated injections of corticosteroids on the development of the optic nerve and reported a disrupted retinal development that persisited days after cessation of treatment and a significant delay in the myelination of the optic axons and thinning of the retina [ 15 , 16 ]. Church et al demonstrated that neonatal rats exhibited prolonged auditory brainstem response latencies reflecting slower neural transmission times along the auditory nerve and brainstem auditory pathway, and associated hearing deficits [ 17 ]. Similar effects may be present to account for the differences seen in the term group of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dunlop and Quinlivan examined the effect of repeated injections of corticosteroids on the development of the optic nerve and reported a disrupted retinal development that persisited days after cessation of treatment and a significant delay in the myelination of the optic axons and thinning of the retina [ 15 , 16 ]. Church et al demonstrated that neonatal rats exhibited prolonged auditory brainstem response latencies reflecting slower neural transmission times along the auditory nerve and brainstem auditory pathway, and associated hearing deficits [ 17 ]. Similar effects may be present to account for the differences seen in the term group of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated a variety of deleterious effects of antenatal administration of highdose dexamethasone on the developing brain, including alteration of nuclear transcription factors and neurotransmitter systems, reduced brain growth, and delayed myelination and maturation of astrocytes (19)(20)(21)(22)(23)(24)(25). Experiments in pregnant non-human primates exposed to betamethasone have also showed delayed myelination of the fetal brain and hippocampal damage (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In MACS-5, infants born at term who were exposed as fetuses to multiple courses of ACS had a higher risk of the composite outcome of death or survival with a neurodevelopmental or neurosensory disability [10]. These findings are consistent with animal studies where repeated ACS treatment was associated with impairment of axonal myelination in the optic nerve, prolonged auditory brainstem responses, and slower neural transmission times [11-13]. …”
Section: Introductionmentioning
confidence: 72%
“…Several animal studies have shown harmful effects of fetal ACS exposure on auditory function [11, 20]. Church et al [11] demonstrated that repeated ACS treatment in rats resulted in a significantly prolonged neuronal transmission time along the auditory nerve and significantly elevated auditory brainstem response thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation